Medical terminology : an illustrated guide - Cohen, Barbara J. (Baltimore, MD : Wolters Kluwer Health / Lippincott Williams & Williams, 2008)
Now in its Fifth Edition, this richly illustrated guide is a comprehensive introduction to medical terminology. It provides extensive coverage of terms related to structure and function, disorders, diagnosis and treatments. It features a user-friendly layout, basic approach to the subject, and numerous learning exercises. This edition includes updated terminology and drug information, an introduction to medical dictionaries, and an appendix on how to use Stedman's Medical Dictionary. A free bound-in CD-ROM contains numerous exercises including Stedman's audio pronunciations and exercises for students. LiveAdvise: Medical Terminology--an online student tutoring and faculty support service--is free with the book. A fully customizable online course created specifically for this text is available as an additional purchase.
Appendix 1. Commonly used symbols -- Appendix 2. Abbreviations and their meanings -- Appendix 3. Word parts and their meanings -- Appendix 4. Meanings and their corresponding word parts -- Appendix 5. Word roots -- Appendix 6. Suffixes -- Appendix 7. Prefixes -- Appendix 8. Metric measurements -- Appendix 9. Stedman's medical dictionary at a glance -- Answer key -- Figure credits -- Index.
Includes bibliographical references and index.
Keywords: Medicine -- Terminology; Terminology as Topic; Terminology